Tunable Unidirectivity of Metal-Dielectric-Metal Plasmonic Nanoantennas With PT-Symmetric Potentials - Xu, Chaowei; Zhang, Xiaoming; Cheng, Kaiyang; Shang, Xiaobing; Li, Quan; Wei, Zeyong; Wu, Chao; Li, Hongqiang (Frontiers in Physics, 2019)
Parity-time (PT) symmetric photonic systems have attracted much attention due to their intriguing properties and asymmetric behaviors. In this paper, we propose a plasmonic nanoantenna with PT-symmetric potential for unidirectional scattering functionality. The studied plasmonic nanoantenna is comprised of three metallic layers separated by two dielectric layers. Such kind of system, with the same coefficient κ of loss and gain in each of the two dielectric layers, holds the characteristic of PT symmetry. We show that the unidirectional scattering is obtained for the passive structure (i.e., κ = 0), and the switching between forward and backward directionality can be achieved with a single structure by changing the excitation wavelength, when the induced electric dipole (ED) and magnetic dipole (MD) modes satisfy the first or second Kerker conditions, respectively. In addition, we find that the forward-to-backward ratio spectra can be strongly affected by the non-Hermiticity parameter κ. In particular, it is possible to reverse the radiation direction at the same wavelength in a wide spectra band by adjusting κ. Moreover, putting the nanoantennas in an array of transverse configuration can efficiently narrow the main lobe angular beam width to be <6°. These results contribute to the basic understanding of the optical properties of active-passive finite nanostructures with potential applications, and provide new ideas for the design of novel nanostructures displaying asymmetric and tunable responses.